Identifying immunity gaps for measles using Belgian serial serology data. Issue 26 (9th June 2022) - Schenk, Julie; Abrams, Steven; Litzroth, Amber; Cornelissen, Laura; Grammens, Tine; Theeten, Heidi; Hens, Niel
Highlights: Measles incidence peaks despite well-established vaccination and high vaccine uptake. Closing immunity gaps is important to improve rapid responsiveness to outbreaks. Investigation of age-specific humoral immunity levels using seroprevalence data. Abstract: Vaccine-preventable diseases, such as measles, have been re-emerging in countries with moderate to high vaccine uptake. It is increasingly important to identify and close immunity gaps and increase coverage of routine childhood vaccinations, including two doses of the measles-mumps-rubella vaccine (MMR). Here, we present a simple cohort model relying on a Bayesian approach to evaluate the evolution of measles seroprevalence in Belgium using the three most recent cross-sectional serological survey data collections (2002, 2006 and 2013) and information regarding vaccine properties. We find measles seroprevalence profiles to be similar for the different regions in Belgium. These profiles exhibit a drop in seroprevalence in birth cohorts that were offered vaccination at suboptimal coverages in the first years after routine vaccination has been started up. This immunity gap is observed across all cross-sectional survey years, although it is more pronounced in survey year 2013. At present, the COVID-19 pandemic could negatively impact the immunization coverage worldwide, thereby increasing the need for additional immunization programs in groups of children that are impacted by this. Therefore, it is now even more important to identify existing immunity gaps and to sustain and reach vaccine-derived measles immunity goals.